Neurologic injuries in hockey - Wennberg, R. A.; Cohen, H. B.; Walker, S. R. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Ice hockey is a fast contact sport played on an ice surface enclosed by rigid boards. There is an intrinsic risk for injury in hockey, with many injuries potentially affecting the nervous system. This article provides an overview of neurologic injuries occurring in hockey as reported in the scientific literature. Among all injuries, a small but real risk for catastrophic cervical spinal cord injury and a high incidence of concussion emerge as the two most important neurologic issues.